2010
DOI: 10.1021/jp9108046
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dissolution and Segregation in Pd(110)

Abstract: The bulk-surface diffusion of carbon in Pd(110) has been investigated using molecular beams to examine the clean-off of carbon with gas-phase oxygen. The dominant product of the reaction above 600 K is CO; CO 2 is only produced at much lower temperatures where the lifetime of adsorbed CO is significant. The segregation from the bulk only occurs at a measurable rate at >750 K, while loss of carbon into the bulk can occur at much lower temperatures. The reaction of carbon at high temperatures shows two regimes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 43 publications
(88 reference statements)
2
26
1
Order By: Relevance
“…Under the CO pulse the Pd lattice undergoes expansion that is interpreted with the formation of PdC x . These data have been supported by independent hard-XRD experiments under similar conditions [18] and agree with other reports [28,29].…”
Section: No Reduction By Co On Pd/al 2 Osupporting
confidence: 92%
“…Under the CO pulse the Pd lattice undergoes expansion that is interpreted with the formation of PdC x . These data have been supported by independent hard-XRD experiments under similar conditions [18] and agree with other reports [28,29].…”
Section: No Reduction By Co On Pd/al 2 Osupporting
confidence: 92%
“…In our work we have observed that there are different processes occurring during the formation of PdC x . Surprisingly, together with dehydrogenation, and in contrast with the behaviour of single crystal Pd, we find that disproportionation of ethene to carbide and methane is a major reaction pathway. The stoichiometry of the carbide phase has been variously reported from a value of PdC 0.05 to PdC 0.16 (though higher levels are reported in the surface regions), but here we find the loading of the carbide to be much higher at ∼28 atom % C.…”
Section: Introductioncontrasting
confidence: 77%
“…Pd is an important catalytic metal and it is used in a variety of processes, for instance, in the Wacker process for the selective oxidation of ethane to acetaldehyde, in vinyl acetate synthesis and in a wide range of fine chemicals hydrogenation reactions, which are often heterogeneous, liquid phase processes. The interaction of ethylene, ethanol, acetic acid and many other simple organic molecules with the surface of Pd can lead to the formation of palladium carbide . This can have an effect on the activity and selectivity of the reaction of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous reports [20][21][22][23][24][25][26] and our comparative studies of Ni(acac) 2 and NiCl 2 led us to conclude that acetylacetonate was the source of carbon present into the solid matrix.…”
mentioning
confidence: 55%